Eksplorasi Konten kuliner oleh Food Vlogger pada Instagram di Marriott Cafe Hotel JW Marriott Medan - M. Ridwan Hanafi; Lise Asnur (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research was conducted because researchers observed that food vlogger content on Instagram social media at the Marriott Cafe Hotel JW Marriott Medan was not effective. The main problem is that the uploaded content still has little insight or interaction such as the number of viewers, likes, and those who share the content, as well as a lack of detail and enthusiasm in explaining the content reviewed by food vloggers. The aim of this research is to analyze the content carried out by 5 food vlogger on social media Instagram Marriott Cafe Hotel JW Marriott Medan. The type of research used was descriptive with a qualitative approach, by interviewing three (3) informants using a purposive sampling technique. Data collection techniques through interviews, observation and documentation., observation, documentation. The data is analyzed by reduction, namely summarizing, selecting and focusing on important things and analyzing the data obtained with the problem being studied. The results of this research show that the content uploaded by food vloggers at the Marriott Cafe is visually and audio and editing is good, but the content, namely the way the food vlogger conveys the message, is less interesting, namely the food vlogger does not use an original voice such as a good, unique, distinctive narrative. in conducting reviews, this is what causes Instagram users to be less interested in watching food vlogger content which causes little engagement on Instagram social media when food vloggers at the Marriott Cafe Hotel JW Marriott Medan.